Tempering Power. How to think, and not to think, about the Rule of Law - Krygier, Martin (EUNOMÍA. Revista en Cultura de la Legalidad, 2023)
The rule of law has been the beneficiary of many more stale words than fresh thoughts. And today its aura has dimmed. Yet it is hugely important to think well about, and I believe there are better ways.  The critical jumping-off point of the argument is a critique of conventional legalistic approaches which, notwithstanding many differences that seem important to their authors, all have in common that they start with the wrong question; go on in the wrong way; and end in the wrong place, with a narrow, parochial lawyers’ answer to a universal social and political (as well as legal) problem. No wonder, as has been said of a good man, the rule of law is hard to find. I argue that if we start and go on differently, we will end closer to a destination worth visiting. That still won’t make the search for the rule of law a walk in the park. However, it might help us avoid being, time and again, mugged by reality. Rather than begin by trying to stipulate what the rule of law is, we should ask what it is for: what’s the point, why that point matters, and what would need to be achieved to make it. Only then can one ask what might be needed to do so. Answers will differ with contexts, times and circumstances. Typically, they will have to go beyond the usual suspects. So, start with the problem and move from there. The specific problem for the rule of law to solve, I contend with no pretence of originality, is arbitrary power. The character of any solution must be to temper (not just limit) power’s exercise to keep arbitrariness to a minimum.  Then the question (the third question, not the first) is how to do that. That, almost certainly and everywhere, will depend on a lot more than conventional rule of law talk suggests. For the ideal of the rule of law is never a purely legal one, but always social and political as well. Solutions will differ, many will not involve, or will go beyond or underlie or stand beside law, and the stakes are high.
Keywords: Rule of Law; arbitrary power; tempering power; anatomical and teleological approaches